REKONFIGURASI JARINGAN PADA SALURAN UDARA TEGANGAN MENENGAH 20 KV PENYULANG NAIONI PT. PLN (PERSERO) ULP KUPANG MENGGUNAKAN PERANGKAT LUNAK ELECTRICAL TRANSIENT ANALYSIS PROGRAM (ETAP) 12.6 - Nikolaus M. Tana; Frans Likadja; Wellem F. Galla (Jurnal Media Elektro, 2019)
The 20 kV medium Voltage overhead lines of Naioni feeder on PT. PLN (Persero) ULP Kupang system has a feed length of ± 79.825 kms and is the longest of all feeders installed in the ULP Kupang. To minimize the voltage drop and power losses on the Naioni Feeder 20 kV medium Voltage overhead lines (SUTM), network reconfiguration needs to be done including changing the diameter of the conductor, installing a transformer insert and installing a capacitor bank using the help of ETAP software. From the results of the study, before reconfiguration, the voltage drop at the end of the Bus_Trafo KB 082 channel was 0.967 kV and the voltage drop percentage was 4.68% while the total power losses at Naioni Feeder were 20 kV, which were active power losses of 48.062 kW and loss reactive power loss of 25,689 kVAR. Furthermore, after reconfiguring the carrying diameter on the channel that still uses a small diameter of 35 mm2, it will be converted to 70 mm2 on cable 17 that connects the KB 119 Transformer Bus channel to the KB 074 Transformer Bus which is a fairly long distance from all other channels. So that after carrying out the reconfiguration of the conductor diameter, the voltage drop at the end of the Bus Trafo KB 082 channel is 0.844 kV and the voltage drop percentage is 4.24%, while the total power losses in the Naioni Feeder are 20 kV which are active power losses of 41.142 kW and conductor reactive power loss of 25.53 kVAR. Furthermore, after installation of the transformer insert and changing the conductor diameter on cable 17 of 35 mm2 will be changed to 70 mm2 connecting the Transformer Bus Channel KB 119 to the KB 074 Transformer Bus, then the voltage drop at the end of the Bus Trafo KB 082 channel is 0.826 kV and the voltage drop percentage amounting to 4.15% while the total power losses at Naioni Feeder are 20 kV, namely active power losses of39.292 kW and reactive power losses of 24.467 kVAR. And then, if the capacitor bank is installed on the Bus Transformer KB 119 channel bus point to the Bus Trafo KB 074 channel, then the voltage drop at the Bus Trafo KB 082 channel end is 0.891 kV and the voltage drop percentage is 4.47%, while the total power losses are The 20 kV Naioni Feeder is an active power loss of 43.714 kW and a reactive power loss of 22.888 kVAR.